2022
DOI: 10.1186/s12885-022-09526-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pyroptosis-related prognostic signature in breast cancer

Abstract: Background The relationship between pyroptosis and cancer is complex. It is controversial that whether pyroptosis represses or promotes tumor development. This study aimed to explore prognostic molecular characteristics to predict the prognosis of breast cancer (BRCA) based on a comprehensive analysis of pyroptosis-related gene expression data. Methods RNA-sequcing data of BRCA were collected from The Cancer Genome Atlas (TCGA) and Gene Expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival. We found our signature have similar short-term survival (3-year) prognostic value compared with them, such as the ferroptosis-related gene signature ( Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ), pyroptosis-related gene signature ( Chen et al, 2022 ), necroptosis-related gene signature ( Yu et al, 2022 ), apoptosis-related gene signature ( Zou et al, 2022 ), zinc finger protein-related gene signature ( Ye et al, 2021 ), autophagy-related gene signature ( Lin et al, 2020 ), and metabolic-related gene signatures ( Lu et al, 2022b ). In addition, our model only involves four genes, while other models (11/13) tend to have more, which is more convenient to use to a certain extent.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival. We found our signature have similar short-term survival (3-year) prognostic value compared with them, such as the ferroptosis-related gene signature ( Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ), pyroptosis-related gene signature ( Chen et al, 2022 ), necroptosis-related gene signature ( Yu et al, 2022 ), apoptosis-related gene signature ( Zou et al, 2022 ), zinc finger protein-related gene signature ( Ye et al, 2021 ), autophagy-related gene signature ( Lin et al, 2020 ), and metabolic-related gene signatures ( Lu et al, 2022b ). In addition, our model only involves four genes, while other models (11/13) tend to have more, which is more convenient to use to a certain extent.…”
Section: Resultsmentioning
confidence: 79%
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, tumor-antagonizing genes could advance our understanding of tumor escape from immune recognition and elimination (Bates et al, 2018). Increasing evidence from studies of bulk RNA-seq data have provided plenty of support for the search of new targets or new therapeutics (Liu et al, 2018;Chen et al, 2022). However, the DEGs from bulk RNA-seq could only represent the average expression levels of the genes.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray (Abd-Elnaby et al, 2021) and next-generation sequencing (NGS) (Hong et al, 2020) technologies provide convenient approaches for gene expression profiling. These technologies have proven beneficial for risk prediction, patient stratification, and mechanism investigation (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation